Legal Politics of Investment Screening in Indonesia’s Foreign Investment Reform - Rahmah, Sherina Azkia; Sihabudin, Sihabudin; Dewantara, Reka (State Islamic University of North Sumatra Indonesia, 2025)
This study aims to examine the significance and regulatory models of investment screening mechanisms in the context of Indonesia's legal and political framework for foreign investment. Employing a normative juridical method combined with a political-legal approach, this research critically analyzes the growing global trend of screening foreign direct investment (FDI) to safeguard national interests. The study finds that Indonesia has yet to establish a coherent legal basis for investment screening, despite increasing strategic and security risks associated with uncontrolled FDI inflows. The absence of a legal framework creates vulnerability in upholding national economic sovereignty and managing foreign capital with precautionary oversight. The research concludes that reforming Indonesia’s investment policy is imperative, not only to ensure regulatory consistency but also to build a national mechanism capable of assessing the potential impacts of foreign investment on strategic sectors. Establishing such a screening regime would align Indonesia with global best practices while preserving its autonomy in economic governance.